Meningkatkan kemampuan guru menggunakan model pembelajaran kooperatif dalam pembelajaran melalui pendekatan supervisi klinis - Ahmad Baihaqi (JPPTK: Jurnal Pendidikan Pembelajaran & Penelitian Tindakan, 2021)
Quality learning in schools is an obligation for teachers in general, however, this is still not done optimally by teachers, and teachers have not been creative in using learning models and new approach techniques. The teacher only conveys the subject matter, lacks control over the condition of the students when learning takes place. The teachers in the average class have not empowered advanced teaching styles and art strategies. The purpose of this school action research is to find out the steps of clinical supervision of clinical supervision (clinical supervision) in improving the ability of teachers to use cooperative learning models at SDN Pemurus Luar 1 Banjarmasin and to determine the improvement of teachers' abilities using cooperative learning models at SDN Pemurus Luar 1 Banjarmasin through clinical supervision. The location for conducting this school action research is at SDN Pemurus Luar 1 Bajarmasin. The subject of this research is the sixth grade teacher. While the research time is planned from January 12 to March 25, 2019. The clinical supervision approach can improve the ability of teachers to use cooperative learning models at Pemurus Luar 1 Elementary School Banjarmasin, such as making academic administration completeness, the ability to create/use media, the ability to compose assessment instruments, the ability to make and develop lesson plans (RPP) well, and the ability to carry out varied learning such as cooperative learning methods. Guidance in clinical supervision carried out by the Principal is carried out from the preparation stage such as looking for problems faced by teachers, collecting data and information and planning activities in carrying out supervision, then the observation stage using observation sheets. The supervisor observes in detail the learning process to find out the teacher's weaknesses in class management and the cooperative method used in accordance with the previously agreed work contract and the final stage or reflection where the supervisor evaluates things that have happened during the observation and the entire cycle of the supervision process with the aim of improve teacher performance.